Comparative Genomics of Nonoutbreak Pseudomonas aeruginosa Strains Underlines Genome Plasticity and Geographic Relatedness of the Global Clone ST235. (3rd July 2018) - Brüggemann, Holger; Migliorini, Leticia Busato; Sales, Romario Oliveira de; Koga, Paula Célia Mariko; Souza, Andrea Vieira de; Jensen, Anders; Poehlein, Anja; Brzuszkiewicz, Elzbieta; Doi, Andre Mario; Pasternak, Jacyr; Martino, Marines Dalla Valle; Severino, Patricia
Abstract: Pseudomonas aeruginosa is an important opportunistic pathogen in hospitals, responsible for various infections that are difficult to treat due to intrinsic and acquired antibiotic resistance. Here, 20 epidemiologically unrelated strains isolated from patients in a general hospital over a time period of two decades were analyzed using whole genome sequencing. The genomes were compared in order to assess the presence of a predominant clone or sequence type (ST). No clonal structure was identified, but core genome-based single nucleotide polymorphism (SNP) analysis distinguished two major, previously identified phylogenetic groups. Interestingly, most of the older strains isolated between 1994 and 1998 harbored exoU, encoding a cytotoxic phospholipase. In contrast, most strains isolated between 2011 and 2016 were exoU -negative and phylogenetically very distinct from the older strains, suggesting a population shift of nosocomial P. aeruginosa over time. Three out of 20 strains were ST235 strains, a global high-risk clonal lineage; these carried several additional resistance determinants including aac(6')Ib-cr encoding an aminoglycoside N-acetyltransferase that confers resistance to fluoroquinolones. Core genome comparison with ST235 strains from other parts of the world showed that the three strains clustered together with other Brazilian/Argentinean isolates. Despite this regional relatedness, the individuality of each of the three ST235 strains was revealed by core genome-based SNPs and the presence of genomic islands in the accessory genome. Similarly, strain-specific characteristics were detected for the remaining strains, indicative of individual evolutionary histories and elevated genome plasticity.